Premature Deaths and Socio-economic Status: The Role of Fine Particulate Matter in Türkiye (2019) - Nilüfer Aykaç; Selin Çakmakcı Karakaya; Merve Erçelik Koncak; Orbay Tutku Seren; Sabri Serhan Olcay; Nil Kader Çağaç; Feride Marım; Susamber Dik; Şule Kızıltaş Bilgin; Maide Gözde İnam; İlknur Kaya; Khurshud Çağla Hüseynova; et al. (Thoracic Research and Practice, 2025)
OBJECTIVE: Air pollution, particularly particulate matter (PM), is a leading environmental risk factor contributing to global morbidity and premature mortality. The World Health Organization’s (WHO) AirQ+© software is a vital tool for assessing the health impacts of air pollution. Our study used this software to estimate premature deaths attributable to long-term particulate matter (PM2.5) exposure in Türkiye in 2019 and explored its relationship with each province’s socio-economic status. MATERIAL AND METHODS: We conducted an ecological study using annual average PM2.5 levels from air quality stations. Due to limited PM2.5 measurements (only 16% of stations), we derived PM2.5 values from PM10 data using WHO’s conversion coefficient for Türkiye. RESULTS: We identified the provinces with the highest PM2.5 concentrations and associated mortality: Iğdır, Şırnak, Çorum, Düzce, and Kahramanmaraş had the highest concentrations, while Erzurum, Çorum, Iğdır, Sinop, and Kütahya had the highest mortality rates per 100,000 population. No significant correlation was found between premature deaths and the socio-economic development index of each province. Our study estimated 37,768 premature deaths attributed to long-term PM2.5 exposure in adequately monitored provinces. CONCLUSION: In 2019, Türkiye faced persistent air pollution, with PM2.5 levels exceeding WHO’s 2021 limits across all provinces and stations. Türkiye lacks specific PM2.5 limits legislation. Our findings provide a fresh insight into the literature, highlighting policy reform needs. However, data deficiencies hindered analysis in some provinces, affecting nearly 20% of the population aged 30 and above and 31% of the total surface area. Therefore, the actual burden of air pollution-related deaths may be higher than our estimates, underscoring the need to address these challenges urgently.